The Effect Of Job Pressure, Organizational Commitment And Job Satisfaction On Employee Performance With Motivation As A Moderating Variable In Rsu Royal Prima Medan - Tarigan, Earnasta; Pakpahan, Efendy; Romy, Elly; Suranta Karo Sekali, Abednego (International Journal of Science, Technology & Management, 2022)
This study aims to partially analyze the effect of job pressure, organizational commitment and job satisfaction on the performance of medical employees and non-medical employees at RSU Royal Prima Medan, analyze the moderating motivation to strengthen the effect of job pressure on the performance of medical and non-medical employees, analyze the moderating motivation to strengthen the influence organizational commitment to the performance of medical employees and non-medical employees, analyzing the moderating motivation to strengthen the effect of job satisfaction on the performance of medical employees and non-medical employees of RSU Royal Prima Medan. This study uses a quantitative description of the instrument questionnaire, the population is 692 medical and non-medical people, the sampling technique of probability sampling is calculated using the Slovin formula so that the number of samples is 87 people. The data analysis technique used the instrument quality test, the use of classical assumptions, moderated linear regression, t test (partial) and F test (simultaneous), the coefficient of determination test.